A comparative analysis of the IFRS prototype standard and current climate-related disclosures by FTSE/JSE financials 15 listed companies in South Africa - Muzata, Tapiwa (International Journal of Business, Economics and Management, 2025)
This study examines the disparity between current climate risk disclosure practices and IFRS S1 and S2 requirements, using the precursor Climate-related Disclosures Prototype Standard as a benchmark. A qualitative, cross-case analysis, and deductive coding approach on archival data of the largest 15 financial companies listed on the FTSE/JSE Financials 15 index, focusing on their 2020 sustainability reports is employed. Key findings underscore a prevalent trend: companies strategically non-disclose climate-related risk scenarios’ results and impacts on business models; they utilise non-economic disclosures, supported by impression management and minimal narrative disclosures; prioritise stakeholder legitimacy and reputation over disclosure of substantive information. This approach, reminisce greenwashing, reluctance to fully disclose climate-related risks, particularly through scenario analysis which exposes diverse CRRO outcomes. Proprietary cost theory might explain this phenomenon. A significant subset of examined companies exhibited distinct lack of disclosure in strategy, and matrices and targets reporting. Non-disclosure patterns have considerable implications of possessing potential to substantially impede climate change and hinder future capital formation. Failure to address identified disparities exacerbates financial risks, heightens reputational risks, impedes business continuity planning, and perpetuates short-termism regarding climate risks issues. Insights in the complex interplay between transparency, reputation, financial concerns, and legitimacy in sustainability reporting are provided.